WordPress Security Masterclass - Defeat Hackers and Malware - Oni, Alexander (Packt Publishing, 2020)
Learn basic to advanced techniques for securing and hardening your WordPress website against hackers and malware About This Video Understand what the .htaccess file is Protect the .htaccess file from unauthorized access Get to grips with changing the default WordPress database table prefix In Detail WordPress security is a critical topic among website owners. With the increasing number of vulnerabilities and attacks that are happening every minute, both companies as well as individuals can be a victim of these breaches. The objective of this course is to teach you both basic and advanced techniques that you can apply to properly secure and harden your WordPress website against hackers and cybercriminals. You'll understand how to identify signs that a website has been compromised. In addition to this, you'll get up and running with applying WordPress security plugins. Later, you'll even understand how you can fix a website that has been compromised. By the end of this course, you'll be well-versed with the essential techniques and have learned how to secure your WordPress website effectively.